Plastics from Bacteria Natural Functions and Applications - Chen, George Guo-Qiang.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The investigation and development of plastics synthesized by bacteria is receiving great attention also due to the raising petroleum prices and many environmental concerns related to plastic pollution. Recent results and studies of the properties and various applications of bio-based plastics are presented in this volume. Polyhydroxyalkanoates (PHAs), a biodegradable compound, is treated in several chapters: PHAs as energy and intracellular carbon storage compounds, the metabolic engineering of PHA producers, the development of tailor-made PHAs including uncommon monomers, microbial PHA production from waste raw materials, PHA polyesters produced by both wild-type and recombinant bacteria and the production of medium-chain-length PHAs in pseudomonads. Further microbial plastics discussed are lactic acid and its polymer polylactic acid (PLA), succinic acid and its polymer polybutylene succinate (PBS), ethylene from ethanol and its polymer polyethylene, 1,3-propandiol as well as poly(p-phenylene) (PPP).
of Bacterial Plastics PHA, PLA, PBS, PE, PTT, and PPP -- Plastics Completely Synthesized by Bacteria: Polyhydroxyalkanoates -- Natural Functions of Bacterial Polyhydroxyalkanoates -- Towards Systems Metabolic Engineering of PHA Producers -- Microbial PHA Production from Waste Raw Materials -- Industrial Production of PHA -- Unusual PHA Biosynthesis -- Metabolic Engineering of Plants for the Synthesis of Polyhydroxyalkanaotes -- Biosynthesis of Medium-Chain-Length Poly[(R)-3-hydroxyalkanoates] -- Nodax$1!" (BClass PHA Copolymers: Their Properties and Applications -- Manufacturing of PHA as Fibers -- Degradation of Natural and Artificial Poly[(R)-3-hydroxyalkanoate]s: From Biodegradation to Hydrolysis -- Microbial Lactic Acid, Its Polymer Poly(lactic acid), and Their Industrial Applications -- Microbial Succinic Acid, Its Polymer Poly(butylene succinate), and Applications -- Microbial Ethanol, Its Polymer Polyethylene, and Applications -- Microbial 1,3-Propanediol, Its Copolymerization with Terephthalate, and Applications -- Microbial cis-3,5-Cyclohexadiene-1,2-diol, Its Polymer Poly(p-phenylene), and Applications.s
Keywords: Life sciences; Biotechnology; Microbiology; Genetic engineering; Bacteriology; Life Sciences; Bacteriology; Applied Microbiology; Biotechnology; Genetic Engineering